Influence of Discipline, Motivation, and Facilities on Employee Performance at Parepare Trade Office - Ibrahim; Mulyana Machmud; Hasanuddin; Badaruddin (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Employee performance in public institutions is shaped by organizational and behavioral factors, with work discipline, motivation, and work facilities being critical in determining productivity and service quality. This study examines the individual and collective impacts of these factors on employee performance at the Trade Office of Parepare City. Using a quantitative approach, the research involved all 45 employees as respondents through a saturated sampling technique. Data were analyzed using multiple linear regression to evaluate the significance of each variable. The findings indicate that work discipline significantly enhances performance, with a t-value of 2.997 exceeding the critical threshold of 2.018. Motivation also has a significant positive effect, evidenced by a t-value of 2.899. However, work facilities show no significant impact, with a t-value of -0.199. Collectively, these variables significantly influence performance, as demonstrated by an F-value of 3.189 surpassing the critical value of 2.82. The study concludes that fostering work discipline and motivation is essential for improving employee performance in public sector organizations, while the role of work facilities appears less impactful when already adequate.